Design, synthesis and cytotoxicity of novel N-benzylpiperidin-4-one oximes on human cervical cancer cells - Dindulkar, Someshwar D.; Bhatnagar, Ira; Gawade, Rupesh L.; Puranik, Vedavati G.; Kim, Se-Kwon; Anh, Dong Hyun; Parthiban, Paramasivam; Jeong, Yeon Tae (Journal of Chemical Sciences, 2014)
A series of fifteen diversified N-benzylpiperidin-4-one oximes were synthesized and characterized by their NMR spectral data. Additionally, single-crystal XRD analysis was performed for the representative symmetrically and unsymmetrically substituted molecules. All the synthesized oximes from unsymmetrical ketones existed as E-isomer as witnessed by their NMR and XRD data. Among the synthesized target compounds that evaluated for their in vitro cytotoxicity against human cervical carcinoma (HeLa) cells, five compounds were potent with IC50 < 17 mu M. 1-Benzyl-2,6-bis(4-isopropylphenyl)-3-methylpiperidin-4-one oxime 3c with an IC50 of 13.88 mu M was found to be the best active compound as depicted by the microscopic analysis.
Keywords: Cytotoxicity; HeLa cells; N-benzylpiperidin-4-one oximes; single-crystal XRD

Disruption of native beta-turns: consequence of folding competition between native and orthanilic acid proline-based pseudo beta-turn - Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Chaitanya, K. N.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2016)
Five tetrapeptides comprising beta-turn-forming elements and a pseudo beta-turn (C9 H-bonding) based on an SAntPro (orthanilic acid - proline) motif were designed and synthesized. Their extensive conformational investigation by single-crystal X-ray crystallography, solution-state 2D NMR spectroscopic, and nOe-restrained MD simulation studies revealed the formation of C14 or C9 folding and disruption of the native beta-turn (C10 H-bonding) architecture. The striking difference between the psi(psi(2)) angle of ``i + 2'' residues of native beta-turn and designed peptides suggest that formation of the native beta-turn is not favored. The results suggest that other turn-forming motifs can dramatically modulate the stability of the native beta-turn structure.
Keywords: Conformation analysis; hydrogen bonds; Peptidomimetics; structure elucidation